Integrating Smart Energy Monitoring and Energy Efficiency Measures to Reduce Carbon Emissions in Institutional Buildings: An Environmental Science and Sustainable Development Approach - B Naveena; Stefanie White (Integrated Science Education Journal, 2026)
Purpose of the study: This study aims to evaluate the impact of implementing smart energy monitoring systems on energy efficiency, operational energy consumption, and carbon emissions in institutional buildings in Montenegro. The research seeks to quantify potential energy savings and emission reductions achieved through real-time monitoring and data-driven optimization. Methodology: This study employs a quantitative case study design using a before–after comparative analysis applied using smart energy monitoring systems installed in public institutional buildings. Historical energy consumption data, energy audits, and building characteristics were analyzed. Energy Use Intensity (EUI) and CO₂ emissions were calculated, and data were processed using descriptive and comparative statistical methods with visualization tools to assess before-and-after impacts. Main Findings: Implementation of the smart monitoring system reduced average EUI by approximately 20% (from 222.5 to 178.0 kWh/m²/year) across four institutional buildings. Daily energy consumption decreased across all time periods, with peak-hour reduction reaching 19%. CO₂ emissions declined by about 20%, mirroring energy savings. Statistical analysis confirmed that the reductions were significant (p < 0.01), demonstrating measurable improvements in operational efficiency. Novelty/Originality of this study: This research provides the first empirical evidence from Montenegro on the effectiveness of smart energy monitoring in public institutional buildings. Unlike prior simulation-based studies, it uses full-year real data to show measurable energy and emission reductions. The findings offer actionable insights for policymakers and building managers, advancing knowledge on sustainable energy management in energy-transition countries.